Designing Web-based English Listening Tasks for University Students - Nurohmawati, Mei; Arini, Restu (CV. Pusdikra Mitra Jaya, 2023)
Some problems faced by the student in listening activities are limited vocabulary, unfamiliar phrases or words, inability to understand the message due to lack of exposure to listening. This study emphasizes the design of English listening tasks using websites to improve students' listening skill. Two main objectives were determined: (1) to present the process and need analysis of the development of web-based listening tasks; (2) to present the appropriateness of the web-based task and students’ improving in listening skill. This study is designed-based research using a mix method. ADDIE model was used as the process of design. The data were qualitative and quantitative which was collected by using questionnaire, observation and test. The result shows students' enhancement of around +11 from the pre test (score 71.75) and the post test (score 83.52). The web-based listening task was considered good by 63% of students. Expert judgments also confirmed score 4.4 for the content or listening tasks that covered the alignment of the content with learning outcomes, materials, originality, and students’ need; and score 4,1 for the media in the terms of instruction, multisensory experience, the visual, the communicative aspects.In conclusion, web-based listening tasks are the answer to improve students’ listening skills and boost their motivation to learn English.